Development of E-Modules Learning Explanatory Text Writing Skill with Discovery Learning Approach for Grade XI - Samsul Arifin; Syahrul Ramadhan (STAI Hubbulwathan Duri, 2025)
The integration of digital learning tools is essential in modern education. This study examines the effectiveness of e-modules using a discovery learning approach to enhance students' skills in writing explanatory texts. This research follows a development research model comprising four stages: (1) Defining, (2) Design, (3) Development, and (4) Deployment. Four instruments were used: needs analysis, e-module validation, e-module practicality assessment, and performance tests. The study was conducted with Class XI students in Tasik Putri Puyu. The findings indicate that the developed e-modules are valid, highly feasible, and effective for classroom use. The discovery learning approach within the e-modules facilitated students' active exploration and knowledge construction, leading to improved writing skills. The results support the use of e-modules as an effective digital learning tool. The discovery learning approach enhances student engagement and comprehension by encouraging investigative learning. These findings align with previous studies highlighting the benefits of digital resources in education. The study concludes that e-modules employing a discovery learning approach significantly improve students' ability to write explanatory texts. Educators are encouraged to integrate such digital tools into their teaching practices to enhance student learning experiences in the digital era.